DETERMINAN NET INTEREST MARGIN BANK UMUM DI INDONESIA: STUDI SAAT TREN PENURUNAN - cindy wanady; caroline wibowo; dahlia ervina (LIAISON JOURNAL OF BEST, 2022)
Net Interest Margin (NIM) rate of banks in Indonesia relatively higher compared to other countries such as Malaysia, Singapore, Thailand, and Philippines. During 2011-2014, there is a significant decrease in NIM rate of banks. Considering this, researchers compelled to do this research with the aim to see the determinants of NIM rate of commercial banks during that period. Cross-subsidiation hypothesis explain that there is a trade off between decreasing NIM with increasing fee-based income (non interest income). This paper focusing on bank-spesific factor, mainly used revenue diversification as proxy for fee-based income, in relation the effect to NIM. The sample used in this paper are 72 commercial banks over 2011-2014 (the only period the NIM consecutively decreasing). Panel Data Regression is used as the research method and Fixed Effect Model as the estimation model to test 3 independent variables, which are operational efficiency, size, and income diversification. The results show that size and income diversification has negative significant effect on NIM. On the other hand, operational efficiency has positive significant effect on NIM.Keywords: Net Interest Margin, Fee-based income, operational efficiency, company size, incomediversification